2022
DOI: 10.3389/fnana.2022.826976
|View full text |Cite
|
Sign up to set email alerts
|

An Update on the Molecular Mechanism of the Vertebrate Isthmic Organizer Development in the Context of the Neuromeric Model

Abstract: A crucial event during the development of the central nervous system (CNS) is the early subdivision of the neural tube along its anterior-to-posterior axis to form neuromeres, morphogenetic units separated by transversal constrictions and programed for particular genetic cascades. The narrower portions observed in the developing neural tube are responsible for relevant cellular and molecular processes, such as clonal restrictions, expression of specific regulatory genes, and differential fate specification, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 258 publications
(486 reference statements)
0
9
0
Order By: Relevance
“…Intriguingly, these observations suggest a mechanistic link between cellular diversification within the cerebellar anlage and its early induction following expression of Fgf8 within the isthmic organizer. To wit, Fgf8 is not only one of the first molecular markers that makes it possible to distinguish midbrain and future cerebellar territory; it is, when expressed ectopically, also capable of inducing the formation of cerebellar cells/tissue (e.g., Hidalgo-Sanchez et al 2022 , and Wassef 2022 for a recent reviews). Conversely, following ablation of Fgf8, neither a cerebellum nor a proper midbrain develops (Sato and Joyner 2009 ; Hörnblad et al 2021 ).…”
Section: Some Notes On Key Genes That Pattern the Cerebellar Ventricu...mentioning
confidence: 99%
“…Intriguingly, these observations suggest a mechanistic link between cellular diversification within the cerebellar anlage and its early induction following expression of Fgf8 within the isthmic organizer. To wit, Fgf8 is not only one of the first molecular markers that makes it possible to distinguish midbrain and future cerebellar territory; it is, when expressed ectopically, also capable of inducing the formation of cerebellar cells/tissue (e.g., Hidalgo-Sanchez et al 2022 , and Wassef 2022 for a recent reviews). Conversely, following ablation of Fgf8, neither a cerebellum nor a proper midbrain develops (Sato and Joyner 2009 ; Hörnblad et al 2021 ).…”
Section: Some Notes On Key Genes That Pattern the Cerebellar Ventricu...mentioning
confidence: 99%
“…This scenario saw the midbrain-pons transition in a more elaborated manner, resolved nowadays in the concepts of a preisthmic m2 segment caudal to m1, followed by a hindbrain prepontine area divided into the isthmus (rh0) and rh1 neuromeres [22,23,34]. The important boundary, in more ways than one, was not the imaginary midbrain-pons limit, but the isthmo-mesencephalic or m2-rh0 limit, to which secondary organizer properties and crucial evolutive intertagmatic roles were later attached (review in [12,35]).…”
Section: The Theoretical and Technical Background Of Present Studiesmentioning
confidence: 99%
“…The isthmus or rhombomere 0 represents the rostralmost prepontine hindbrain neuromeric unit [6,8]. It was shown that transplanting pieces of the isthmic alar neuroepithelium ectopically anywhere in the competent diencephalo-mesencephalo-rhombencephalic domain (from the zona limitans intrathalamica to the rhombospinal boundary) generates ectopic copies of the cerebellum [2,[9][10][11][12].…”
Section: Introduction the Isthmic Organizer And The Preisthmusmentioning
confidence: 99%
See 1 more Smart Citation
“…Brainstem development is an evolutionary conserved process that begins with the specification of the mesencephalon (midbrain) and rhombencephalon (hindbrain) by the isthmic organizer. This organizer is located at the midbrain-hindbrain border and produces diffusible morphogens (particularly Wnt1 and Fgf8 ligands) that act directly on the neighboring nervous tissue to impose midbrain and hindbrain cell fates ( Zervas et al, 2004 ; Dworkin et al, 2012 ; Gibbs et al, 2017 ; Gutzman et al, 2018 ; Hidalgo-Sanchez et al, 2022 ). Various transcription factors are differentially expressed anterior and posterior to the isthmic organizer, such as the antagonistic homeodomain factors Otx2 (anterior) and Gbx2 (posterior), whose expression defines the rostral and caudal regions of the developing central nervous system ( Figure 1A ; Millet et al, 1996 , 1999 ; Broccoli et al, 1999 ; Hidalgo-Sanchez et al, 1999 ; Joyner et al, 2000 ; Katahira et al, 2000 ; Di Giovannantonio et al, 2014 ).…”
Section: Anterior To Posterior Patterning Of the Developing Brainstemmentioning
confidence: 99%